2015
DOI: 10.21098/bemp.v18i2.520
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Bank's Efficiency in Indonesia

Abstract: This paper measures the efficiency of the banks using the intermediation approach and the Data Envelopment Analysis (DEA) on quarterly data of 108 conventional banks in Indonesia during the period of 2012Q1 to 2014Q4. The results shows that the Indonesian banking industry is inefficient in its intermediation function, which is in line with their financial indicators namely the total increasing asset, stable ROA of around 2-3%, and their Operating to Income Cost ratio of about 66-83%. Furthermore, we apply data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 13 publications
4
27
0
9
Order By: Relevance
“…Semakin besar pembiayaan yang disalurkan BUS, semakin optimal BUS menjalankan fungsinya sebagai lembaga intermediasi. Hal yang sama juga ditemukan pada penelitian yang dilakukan Widiarti et al (2015). ROE mewakili tingkat profitabilitas suatu BUS.…”
Section: Efisiensi Bank Umum Syariah DI Indonesiaunclassified
“…Semakin besar pembiayaan yang disalurkan BUS, semakin optimal BUS menjalankan fungsinya sebagai lembaga intermediasi. Hal yang sama juga ditemukan pada penelitian yang dilakukan Widiarti et al (2015). ROE mewakili tingkat profitabilitas suatu BUS.…”
Section: Efisiensi Bank Umum Syariah DI Indonesiaunclassified
“…The greater the funds owned by a bank, it is also accompanied by the large opportunities for the bank to carry out its activities in achieving its objectives (Nandadipa, 2010). Several authors have conducted similar studies with research conducted by the author on the performance of this bank, including by (Parenrengi & Hendratni, 2018), (Pardede, 2016), (Haryoso & Kusdiasmo, 2016), (Yanti & Masdjojo, 2018), and (Widiarti, Siregar, & Andati, 2015), regarding the analysis of several variables, which influence different variables in each study of bank performance.…”
Section: I1 Introduction and Research Rationalementioning
confidence: 82%
“…Muazaroh et al (2012) used the SFA approach and found that bank profit efficiency was positively influenced by bank size, capital, foreign ownership, and market share and negatively influenced by listing on the stock exchange. Widiarti et al (2015) used the DEA technical efficiency approach and the panel data common effects approach during the period 2012-2014 and found that bank technical efficiency was positively affected by bank size and capital, and negatively affected by NPL and the cost/efficiency ratio.…”
Section: Determinants Of Bank Technical Efficiencymentioning
confidence: 99%
“…No articles have been published that comprehensively review the efficiency level of RDBs at the same time as examining the determinants. Widiarti et al (2015) was the only study to have examined the level of efficiency of commercial banks in Indonesia using the DEA approach and then analyze its determinants. They studied bank efficiency during the period 2012-2014 and revealed that it was positively affected by bank size and capital, and negatively affected by NPL and the cost/ efficiency ratio.…”
Section: Introductionmentioning
confidence: 99%